CORPORATE GOVERNANCE, KARAKTERISTIK PERUSAHAAN DAN ENVIRONMENTAL DISCLOSURE - Suhardjanto, Djoko (PRESTASI, 2010)
The purpose of this study is to examine relationship between corporate governance, company characteristics and its environmental disclosures. Corporate governance are identified as the proportion of independent commissioner, the ethnic of commissioner president, the educational background of commissioner president, the number of commissary board meeting, the proportion of independent audit committee, and the number of audit committee meeting. Company characteristics are indentified as size, leverage, profitability, and companyâs operation territory. Companiesâ environmental disclosures are measured by using the Indonesian Environmental Reporting index that developed by Suhardjanto, Tower and Brown (2007). Under proportional random sampling method, 90 Indonesian listed companiesâ annual reports are selected. From the sample, there is fourthy seven point seventy eight percent (47.78%) disclosed environmental information with level of five point thirty five percent (5.35%). This study employed logistic regression and multiple regression. Analysis of statistical results cultural background of president commissioner, Size, leverage as powerful variables to predict the level of environmental disclosure. In addition, cultural background of president commissioner, leverage and Profitability are as determinants to predict environmental disclosure.Keywords: Corporate governance, company characteristics, independent commissioners, independent audit committee, environmental disclosure, Indonesian Environmental Reporting (IER) index.